On signed product cordial of lemniscate graph and its second power - Shokry Nada, Ashraf Elrokh, Atef Abd El-hay (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A graph is called signed product cordial graph if it is possible to label the vertex by the function and label the edges by , where , so that and . In this paper we present necessary and sufficient conditions for which lemniscate and its second power are signed product cordial graph.